Non-isotopic mapping of ribosomal RNA synthesis and processing in the nucleolus - Stanek, D; Koberna, K; Pliss, A; Malínský, J; Masata, M; Vecerová, J; Risueño, M C; Raska, I (Chromosoma, 2001)
The precise location of ribosomal RNA (rRNA) synthesis within the nucleolus is the subject of recent controversy; some investigators have detected nascent RNA in the dense fibrillar components (DFCs) while others have localized transcription to the fibrillar centers (FCs). We endeavored to resolve this controversy by applying a new technique for non-isotopic labeling of RNA and examined the synthesis and movement of non-isotopically labeled rRNA within the nucleolus. We found that rRNA is synthesized only in a restricted area of DFCs, also involving the boundary region with FCs. We traced a movement of RNA from transcription sites through DFCs to granular components. Our results indicate functional compartmentalization of DFCs with respect to the synthesis and processing of precursor rRNA. In situ mapping of the 5' leader sequence of the 5' external transcribed spacer together with transcription labeling indicated that transcription and the first steps in processing of precursor rRNA are spatially separated. Surprisingly, the results also pointed to a partially extended conformation of newly synthesized precursor rRNA transcripts.
Keywords: hybridizace in situ; Chromosomal Proteins, Non-Histone; Microscopy, Immunoelectron; RNA Processing, Post-Transcriptional; fluorescenční protilátková technika přímá; Cell Nucleolus; Transcription, Genetic; posttranskripční úpravy RNA; In Situ Hybridization; prekurzory RNA; RNA, Ribosomal; králíci; HeLa buňky; luminescentní proteiny; genetická transkripce; zelené fluorescenční proteiny; Animals; RNA Precursors; lidé; ženské pohlaví; HeLa Cells; RNA ribozomální; Humans; imunoelektronová mikroskopie; zvířata; Rabbits; Green Fluorescent Proteins; myši; Fluorescent Antibody Technique, Direct; Luminescent Proteins; chromozomální proteiny, nehistonové; Mice; Female; buněčné jadérko